Phytochemical Profiling and In Vitro Anticancer Activity of Purified Flavonoids of Andrographis glandulosa - Cherukupalli, Neeraja; Bhumireddy, Sudarshana Reddy; Akella, Subrahmanya Sarma V; Sataniya, Aaysha; Sripadi, Prabhakar; Khareedu, Venkateswara Rao; Vudem, Dashavantha Reddy (Planta Medica International Open, 2017)
The genus Andrographis includes diverse species of medicinal importance. The present study for the first time unravels the chemical profiling and medicinal importance of an unexplored species, Andrographis glandulosa. LC-MS analysis of A. glandulosa methanolic extract disclosed it as a rich source of flavonoids, with 8 minor peaks and 2 major peaks (m/z 285.0749 and 283.0595). NMR and ESI-MS/MS analyses confirmed the major peaks as (R) 2',5-dihydroxy-7-methoxyflavanone and 2',5-dihydroxy-7-methoxyflavone. Purified compounds exhibited antiproliferative activity on 3 cancer cell lines (HeLa, MIA PaCa and U-87) with IC50 39.81–46.21 µM for flavanone, and 20.84–25.16 µM for flavone. IC50 values of flavone are on a par with that of the positive control quercetin (21.78–26.82 µM). HeLa cells treated with 117 µM flavanone showed a loss of MMP (~55% of cells) resulting in apoptosis (~51% of cells). Treatment with 80 µM flavone caused a loss of MMP (~88% of cells) and induced apoptosis in ~70% of cells proving its efficacy over flavanone. Purified flavonoids exhibited cytotoxicity by disrupting mitochondrial membrane, caspase 3 activation and apoptosis. Purified flavonoids appear as promising natural products for developing cancer therapeutics.
Keywords: Andrographis glandulosa; Acanthaceae; chemical profiling; LC-MS; NMR-spectroscopy; ESI-MS/MS; anticancer activity